Why Halal Awareness Matters in Supporting Sustainable Halal Cosmetics? - Asiyah, Binti Nur; Adlan, Muhamad Aqim; Mashudi, Mashudi; Huda, Qomarul; Hidayat, Muhammad Syahrul; Holle, Moh. H.; Wahyudi, Amin; Kinanti, Karunia (Fakultas Ekonomi, UIN Maliki Malang, 2025)
This study aims to analyze the role of awareness of halal products as a factor influencing consumer decisions to buy halal products, in order to support the sustainability of the halal cosmetics industry, especially the Wardah brand. The halal industry not only sells value branding but also ensures the availability of a sustainable supply of halal products. This paper was studied using a quantitative approach, with a causal associative method. Data analysis techniques include validity, reliability, classical assumption tests, and hypothesis testing using multiple regression and path analysis. The research results show that product knowledge and religiosity positively affect halal product purchases; product knowledge alone has no significant impact. Religiosity negatively affects purchasing decisions; product knowledge boosts halal awareness; religiosity negatively impacts halal awareness. Simultaneously, product knowledge, religiosity, and halal awareness significantly influence purchases; product knowledge has a positive but insignificant effect on purchases via halal awareness, and religiosity significantly negatively affects purchases through halal awareness. The halal industry should focus on enhancing consumer halal awareness to influence purchasing decisions among Muslims and non-Muslims, aiming to improve supply chain productivity for sustainability